Rola polskojęzycznych mediów lokalnych w krzewieniu kultury polskiej w Łatgalii (na Łotwie) - Rubene, Diana (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The paper presents information about the Polish media in the Latgale region – an area with the largest concentration of Poles in Latvia. Media of this type operate with the support of, among others, the Polish Senate and various foundations. The beginnings of the Polish-language media in Latgale date back to the late 1990s. In cooperation with different Polish organizations, Polish media in the region (mainly radio and television) activate and integrate the Polish diaspora, as well as provide information about the everyday life of Poles in Latgale. What is more, such media play an important role in popularizing the Polish language and culture.